Structure and Diversity of Mobile Macro-invertebrate Assemblages Associated to Different Seaweeds - Bedini, Roberto; Bedini, Marco; Bonechi, Lisa; Piazzi, Luigi (European Journal of Applied Sciences, 2024)
The study aimed at comparing the structure of mobile macro-invertebrate assemblages associated with two different Cystoseira species and with algal turf. A total of 138 taxa were identified: 27 Polychaeta, 62 Arthropoda, 35 Mollusca, 4 Echinodermata, 6 Sipuncula, 4 Nemertea. Results showed that assemblages associated to Cystoseira had higher abundance, higher diversity and different structure if compared to those associated to algal turfs. In particular, Mollusca and Crustacea were more abundant in Cystoseira stands and Polychaeta were more abundant in the turf. Moreover, assemblages associated with the two Cystoseira species differed among them for the relative abundance of Mollusca and Crustacea.